An Assessment of the Potential for Controlling Endoparasitism in White-Tailed Deer Via Drugs Incorporated in Bait - Weinstein, Charles E. (University of Wisconsin-Stevens Point, College of Natural Resources, 1976)
The prevalence of endoparasites in a central Wisconsin population of white-tailed deer (Odocoileus virginianus) was determined by fecal examination and necropsy techniques from July 1975 to June 1976. Deer were infected with stomach worms, Haemonchus contortus, Trichostrongylusaxei, and Ostertagia sp.; the menigeal worm, Parelaphostrongylus tenuis; lungworm, Dictyocaulus viviparus; capillary worm, Capillaria sp.; whipworm, Trichuris ovis; thread-necked worm, Nematodirus filicollis; nodular worm, Oesophagostomum venulosum; mesentary worm, Setaria yehi; common tapeworm, Taenia hydatigena; and three species of the coccidian, Eimeria: E. mccordockii, E. madisonensis, and E. odocoilei. Prevalences were generally highest in summer and lowest in winter. Although 10 of these parasites have been reported from livestock, the impact of deer-livestock associations on this deer population could not be assessed. Two concentrations of Rhodamine B dye-labeled com, 0.1 percent and 0.5 percent by weight, were easily formulated and readily consumed by penned white-tailed and fallow deer (Dama dama). The 0.5 percent dosage was detected in all sample fecal pellets by its brilliant orange fluorescence under long-wave ultraviolet light 48 and 72 hours after bait consumption. As a result, the 0.5 percent dosage was used in field studies to determine the portion of a wild deer population that consumed bait during winter 1976. As indicated by the presence of Rhodamine 3 dye in sample fecal pellets for two trials, 85.5 percent and 86.5 percent of the deer population on the Jordan Swamp study area consumed the dye labeled corn. Deer were live-trapped, marked, and released, and a recapture frequency was obtained by aerial observation during winter 1976. The deer population in the study area was estimated to be 10.8 (0.9-15.6, p<0.05) deer/km^2 by a Schnabel Estimate and 12.9 (2.9-46.9, p<0.05) deer/km^2 by a Lincoln Index. These estimates compare well with an overwinter population estimate of 12.4 (2.9-21.9, p<0.05) deer/km^2 obtained from a spring pellet-group count. Based on the labeled bait consumption results, the potential for controlling endoparasitism in white-tailed deer via drugs incorporated in baits was assessed as excellent.